(3GdeO hGdLRQ Hjf GdSQjI GdeUQajI hJHjjV GdGehGds - (3gjGe(B, (3GdLQOs ((3HjQhJ(B:s (3efThQGJ GdMdHj(B,s, 2004)
(3JbOje(B-(3GdbSe GdChd (B: (3GdJYQja HGdeUGQa hGdbGfhf GdeUQaj hYedjGJg (B: (3GdHGH GdChd (B: (3GdaUd GdChd (B: (3GdJYQja HGdeUGQa (B: (3GdaUd GdKGfj (B: (3GdYde HGdbGfhf GdeUQaj hYedjGJg (B: (3GdHGH GdKGfj (B: (3GdaUd GdChd (B: (3GdJYQja HGdSQjI GdeSQajI (B: (3GdaUd GdKGfj (B: (3QaY GdSQjI GdeUQajI (B: (3GdabQI GdGhdi (B: (3MGdGJ QaY GdSQjI GdeUQajI(B-(3GdbSe GdKGfj (B: (3eGgjI ZSd GdCehGd hLQjeI ZSd GdCehGd (B: (3GdHGH GdChd (B: (3eGgjI ZSd GdCehGd GdedhKI (B: (3GdaUd GdChd (B: (3ZSd GdCehGd heagheg (B: (3GdaUd GdKGfj (B: (3ef jbhe HZSd GdCehGd (B: (3GdaUd GdKGdK (B: (3ee JfJL GdCehGd GdedhKI (B: (3GdaUd GdQGHY (B: (3eQGMd ZSd GdCehGd (B: (3GdHGH GdKGfj (B: (3LQjeI ZSd GdCehGd GdedhKI(B-(3GdbSe GdKGdK (B: (3hGbY ZSd GdCehGd YHQ GdYGde hJLGQH HYV GdOhd aj ecGaMI YedjGJ ZSd GdCehGd (B: (3GdHGH GdChd (B: (3hGbY ZSd GdCehGd YHQ GdYGde MGdGJ hCeKdI (B: (3GdeHMK GdChd (B: (3LeghQjI eUQ (B: (3GdeHMK GdKGfj (B: (3efWbI GdNdjL GdYQHj (B: (3GdeHMK GdKGdK (B: (3LeghQjI dHfGf (B: (3GdHGH GdKGfj (B: (3ecGaMI YedjGJ ZSd GdCehGd(B.s
(3HjHdjhZQGajG U(B.375(3; edGMb U(B.195s
Keywords: (3GdHfhc(B--(3bhGfjf hJTQjYGJs; (3GdLQGFe GdGbJUGOjIs; (3GdfbhO(B--(3bhGfjf hJTQjYGJs; (3LQGFe GdCehGds